Influence of Russian and Nato Rivalry on Ukrainian National Security during Volodymyr Zelensky's Presidential Term - Yulia Rimapradesi; Naqia Salsabila Taslim; Riza Putra (Journal of Islamic World and Politics)
Since before the Cold War and until the fall of the Soviet Union, there have been tense relations between Russia and NATO. Russia, which succeeded the Soviet Union as its heir, inherited a few privileges due to its downfall. Russia grew to be the most prominent, prosperous, and richest nation among the CIS nations, having a significant political impact on Eastern and Central Europe. As NATO, a security agreement, increases its influence, Russia feels threatened and does not want to cease to exist. The rivalry between the two actors affects neighboring Russia, including Ukraine. Zelensky's decision to speed up the integration process of the NATO security pact provoked Russian outrage because it was articulated as a challenge, and practically, the actions taken by Zelensky could not accelerate his membership in NATO. Russia launched a military invasion of Ukraine that had implications for the neighboring country's national security crisis. In analyzing this thesis, the authors used the concept of rivalry to analyze the relationship between Russia and NATO and the idea of national security to analyze the status quo of Ukraine due to Russian-NATO influence. The research method was descriptive, using data from books, journals, and several other references. This study found a Ukrainian national security crisis in the Zelensky era due to the influence of Russian and NATO rivalries.